Diagnostic implication of a circulating serum-based three-microRNA signature in hepatocellular carcinoma - Yousuf, Tahira; Dar, Sadaf Bashir; Bangri, Sadaf Ali; Choh, Naseer A.; Rasool, Zubaida; Shah, Altaf; Rather, Rafiq Ahmed; Rah, Bilal; Bhat, Gh Rasool; Ali, Shazia; Afroze, Dil (Frontiers in Genetics, 2022)
Owing to the diagnostic dilemma, the prognosis of Hepatocellular Carcinoma (HCC) remains impoverished, contributing to high mortality rate globally. Currently, HCC diagnosis depends on the combination of imaging modalities and the measurement of serum alpha-fetoprotein (AFP) levels. Nevertheless, these conventional modalities exhibit poor performance to detect HCC at early stages. Thus, there is a pressing need to identify the novel circulating biomarkers to promote diagnostic accuracy and surveillance. Circulating miRNAs are emerging as promising diagnostic tools in screening various cancers, including HCC. However, because of heterogenous and at times contradictory reports the universality of miRNAs in clinical settings remains elusive. Consequently, we proposed to explore the diagnostic potential of ten miRNAs selected on the candidate-based approach in HCC diagnosis. The expression of 10 candidate miRNAs (Let-7a, miR-15a, miR-26a, miR-124, miR-126, miR-155, miR-219, miR-221, miR-222 and miR-340) was investigated in serum and tissue of 66 subjects including 33 HCC patients and 33 healthy controls (HC) by rt-PCR. Receiver operating characteristic curve (ROC) analysis was used to determine the diagnostic accuracy of prospective serum miRNA-panel. To anticipate the potential biological roles of the three-miRNA signature, the target genes were evaluated using the Kyoto Encyclopedia of Genes and Genomes (KEGG) signalling pathway. The serum and tissue expression of miRNAs (Let-7a, miR-26a, miR-124, miR-155, miR-221, miR-222, and miR-340) were differentially expressed in HCC patients (p < 0.05). The ROC analysis revealed promising diagnostic performance of Let-7a (AUC=0.801), miR-221 (AUC= 0.786) & miR-2 (AUC=0.758) in discriminating HCC from HC. Further, in a logistic regression equation we identified a three-miRNA panel (Let-7a, miR-221 & miR-222; AUC = 0.932) with improved diagnostic efficiency in differentiating HCC from HC. Remarkably, the combination of AFP and three-miRNA panel offered a higher accuracy of HCC diagnosis (AUC= 0.961) than AFP alone. The functional enrichment analysis demonstrated that target genes may contribute to pathways associated with HCC and cell-cycle regulation, indicating possible crosstalk of miRNAs with HCC development. To conclude, the combined classifier of three-miRNA panel and AFP could be indispensable circulating biomarkers for HCC diagnosis. Further, targeting predicted genes may provide new therapeutic clues for the treatment of aggressive HCC.